1911 N.Y. Laws 442-43, ch. 195, § 1 - (:unkn) unknown (General Publisher, 1911)
Prohibited the manufacture, sale, giving, or disposing of any weapon of the kind usually known as a blackjack, slungshot, billy, sandclub, sandbag, bludgeon, or metal knuckles, and the offering, sale, loaning, leasing, or giving of any gun, revolver, pistol, air gun, or spring-gun to a person under the age of 16.
--
Keywords: TRANSFER - MINORS